Perfluoroalkyl substances in sediments from the Bering Sea to the western Arctic: Source and pathway analysis. (June 2020) - Lin, Yan; Jiang, Jheng-Jie; Rodenburg, Lisa A.; Cai, Minggang; Wu, Zhai; Ke, Hongwei; Chitsaz, Mahdi
Graphical abstract: Highlights: PFASs in surface sediment were dominated by PFOS and PFNA. Individual PFASs exhibited different temporal variations. Sediments might act as important reservoir and direct sources to food web. Emission sources and transport pathways were assigned and quantified by PMF model. Abstract: Although perfluoroalkyl substances (PFASs) are ubiquitous in the Arctic, their dominant pathways to the Arctic remain unclear. Most modeling studies support major oceanic transport for PFASs in the Arctic seawater, but this conclusion contradicts the rapid response of PFASs to global emissions in some biota species. Sediments, which act as important PFAS sinks for seawater and potential PFAS source to the benthic food web, are important for interpreting the fate of PFASs in the Arctic. Here we investigate the occurrence of 9 PFASs in one core (1945–2014) and 29 surface sediments from the Bering Sea to the western Arctic. Total PFAS concentrations (0.06–1.73 ng/g dw) in surface sediments were dominated by perfluorooctane sulfonate (PFOS), perfluorononanoic acid (PFNA) and perfluorobutyl sulfonate (PFBS), with higher levels in the Bering Sea slope and the northeast Chukchi Sea. Historical trends in PFASs varied among individuals, with PFOS declining in the early 2000s while PFNA showing an increasing up-core trend. Analysis of positive matrix factorization model identified that the major PFAS sources in the sediment core were dominated by the atmospheric oxidation of consumer use of PFOS precursor-based products (45.0%), while the oceanic transport of fluoropolymer manufacture of polyvinylidene fluoride (mainly PFNA) exhibited an increasing trend over time, becoming dominant in surface sediments (42.8%). Besides, local input of possible aqueous fire-fighting foams (mainly PFOS and PFBS) also acted as an important source currently (30.1%) and historically (34.9%). Our study revealed that the pathways of PFASs in Arctic sediments varied greatly for individuals and the conclusion of PFOS originating from mainly atmospheric oxidation was different from seawater modeling results. This, together with the high possibility of sediments as direct source to Arctic food web (supported by similar PFAS compositions and temporal variations), help provide additional evidence regarding PFAS pathways to the Arctic.